The Lysobacter capsici AZ78 Genome Has a Gene Pool Enabling it to Interact Successfully with Phytopathogenic Microorganisms and Environmental Factors - Puopolo, Gerardo; Tomada, Selena; Sonego, Paolo; Moretto, Marco; Engelen, Kristof; Perazzolli, Michele; Pertot, Ilaria (Frontiers in Microbiology, 2016)
Lysobacter capsici AZ78 has considerable potential for biocontrol of phytopathogenic microorganisms. However, lack of information about genetic cues regarding its biological characteristics may slow down its exploitation as a biofungicide. In order to obtain a comprehensive overview of genetic features, the L. capsici AZ78 genome was sequenced, annotated and compared with the phylogenetically related pathogens Stenotrophomonas malthophilia K729a and Xanthomonas campestris pv. campestris ATCC 33913. Whole genome comparison, supported by functional analysis, indicated that L. capsici AZ78 has a larger number of genes responsible for interaction with phytopathogens and environmental stress than S. malthophilia K729a and X. c. pv. campestris ATCC 33913. Genes involved in the production of antibiotics, lytic enzymes and siderophores were specific for L. capsici AZ78, as well as genes involved in resistance to antibiotics, environmental stressors, fungicides and heavy metals. The L. capsici AZ78 genome did not encompass genes involved in infection of humans and plants included in the S. malthophilia K729a and X. c. pv. campestris ATCC 33913 genomes respectively. The L. capsici AZ78 genome provides a genetic framework for detailed analysis of other L. capsici members and the development of novel biofungicides based on this bacterial strain.